Amylase Production By A Thermophilic Bacterium, Bacillus Licheniformis BT5.9 Isolated From Changar Hot Spring, Malang Indonesia - Han , Li Zhu (2012)
This study was carried out in order to search for thermophilic microorganisms with special interest as a source of thermostable amylases. Six samples which consisted of soils, water and sludge were taken from Changar Hot Spring in a volcanic area of Malang, Indonesia. The samples had temperature of 49.5 to 56.0ºC and pH of 5.7 to 6.5. Thirteen out of 34 of bacterial isolates were obtained from those samples and exhibited potential amylase producer, and isolate BT5.9 which was identified as Bacillus licheniformis BT5.9 through biochemical tests and 16S rRNA molecular analysis was chosen as the best amylase producer.